Pengaruh Filtrasi Zeolit dan Arang Aktif Terhadap Penurunan Kadar Fe Air Sumur Gali Di Dusun Morangan, Sindumartani - Defi Asri Handayani; Hapsoro Satrio Wibowo; Ananda Eka Cahyati; May Chindy Pradika Aulia; Ana Zufrida; Rizki Amalia; Sri Haryanti (JPS : Jurnal Pengabdian Serulingmas, 2022)
Water is one that is very important for human life and other living things. Not everyone can get good water quality and sufficient quantity of water to get their daily clean water needs. Based on the problems that exist in Morangan Hamlet accompanied by data from the Ngemplak I Health Center, the quality of the community dug wells in the village does not meet the requirements. Students of the Diploma Three Sanitation Study Program, Environmental Health Polytechnic, Yogyakarta Ministry of Health conducted a Field Work Practice (PKL Komunitas) with several activities related to a survey, analysis, planning, solving socialization problems and practice of implementing clean water, which aims to find out how to trat water to reduce Fe levels in the soil. Community wells. The data obtained from these activities were analyzed descriptively to describe the decrease in Felevels before and after filtration. Based on the Field Work Practice, it was found that the Fe content after filtration was 0,2 mg/L. The results of the activity show that zeolite and activated charcal can be used as materials for iron filtration.